2017
DOI: 10.1080/19401493.2017.1322637
|View full text |Cite
|
Sign up to set email alerts
|

Numerical estimation and sensitivity analysis of the energy demand for six industrial buildings in France

Abstract: When it comes to dealing with energy savings in buildings, studies almost systematically focus on the residential and tertiary building stocks while the industrial building stock is ignored. This study comes as a first step to move forward on this topic and its objectives are threefold: first to develop a simple methodology suitable for various industrial activities, then to analyse the distribution of the energy demand by use for 6 different cases and, finally, to carry out a sensitivity analysis. A first obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although uncertainty and sensitivity analyses have been conducted by many authors on building energy performances [2][3][4][5][6][7][8][9][10][11], few publications discuss the effect of input parameter uncertainties on residential building indoor air quality. Laverge et al [12] compared different mechanical exhaust ventilation systems in accordance with five standards on five different dwelling typologies.…”
Section: Introductionmentioning
confidence: 99%
“…Although uncertainty and sensitivity analyses have been conducted by many authors on building energy performances [2][3][4][5][6][7][8][9][10][11], few publications discuss the effect of input parameter uncertainties on residential building indoor air quality. Laverge et al [12] compared different mechanical exhaust ventilation systems in accordance with five standards on five different dwelling typologies.…”
Section: Introductionmentioning
confidence: 99%
“…Another comprehensive study is the one carried out in France by Labat and Attonaty [14], they found that the energy requirements from heating, ventilation, and air conditioning (HVAC), and lighting systems are of a similar order of magnitude. The analysis was made for six buildings of different uses: warehouses (2), two manufacture buildings (2), food industry (1), and a cattle facility (1).…”
Section: General Measures For Limiting Heat Gains and Losses On Buildmentioning
confidence: 99%
“…After the annual cost from the consumption of both fuels in the buildings is calculated, the annual increment of the prices is also added. The present worth (PW) is estimated with Equation (14) to determine the total cost of the air conditioning systems operation and evaluate its financial feasibility [56].…”
Section: Economic Parametersmentioning
confidence: 99%
See 2 more Smart Citations